Analisis Yuridis Sengketa Perdagangan Antara Amerika Serikat Dan China Dikaitkan Dengan Eksistensi World Trade Organization Sebagai Organisasi Perdagangan Internasional - Sianipar, Dewi Sartika Bulan; Kusuma, Zulfikar Jaya; Diana, Ledy (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
International trade law aims to provide legal certainty and create order for international law subjects. One source of international trade law is GATT which is now replaced by the WTO. In an effort to meet needs through international trade, trade disputes often arise as happened between the two developed countries the US and China. In this case, the United States issued a policy of raising tariffs for various products from China. China also responded by raising tariffs for various products from the US. The actions of these two countries are called tariff wars or trade wars. In the GATT, tariff regulation is regulated in Article II of the GATT on the concession schedule. Where according to Article II of the GATT, the state must not increase arbi-trary tariffs without prior negotiations. in addition to regulating tariffs one of the main activities of the GATT / WTO is as the organizer of a dispute resolution forum in case of violations of the rights and obligations of member countries. The purpose of writing this thesis, namely: first, to find out the United States tariff increase policy is a violation of GATT / WTO rules, second, to find out the existence of the World Trade Organization in resolving trade disputes between the United States and the United States. China. This type of research is normative legal research using research methods on legal principles. Data collection techniques in this study with the study of literature. From the results of the research problem there are two main things that are conclud-ed. First, the US policy in raising import tariffs on China is a violation of the WTO regulatory framework and also some of the principles that exist in the WTO such as the binding tariff principle and the principle of protection through tariffs. second, the stage of dispute resolution that has been passed by the US and China is consultation between the two countries. The WTO does not have an active role in resolving trade disputes between the US and China because of the vacant position in the WTO ap-peals body which makes the WTO's role as a dispute resolution forum unable to run optimally.Keywords : Trade War -Tariff - United Nations - China- dispute resolution